2011
DOI: 10.1557/mrs.2011.132
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonics and nanophotonics for photovoltaics

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 66 publications
0
59
0
Order By: Relevance
“…Recently, an efficiency increase up to several percent has been observed in multi-crystalline silicon cells covered with not densely distributed gold or silver nanoparticles with radius of several tens of nanometers [9]. It must be emphasized that such an increase is very promising in view of other photovoltaic technology, like thin film solar cells, organic plastic cells or newly developed perovskite cells, where an increase even by a few percent would be important to obtain industrially competitive cell designs [4,7,[10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an efficiency increase up to several percent has been observed in multi-crystalline silicon cells covered with not densely distributed gold or silver nanoparticles with radius of several tens of nanometers [9]. It must be emphasized that such an increase is very promising in view of other photovoltaic technology, like thin film solar cells, organic plastic cells or newly developed perovskite cells, where an increase even by a few percent would be important to obtain industrially competitive cell designs [4,7,[10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, OPV devices enhanced by incorporated metallic NP have become one of the most intensively studied topic in OPV research [1,2]. The basic principle behind NP-incorporated OPV devices is the application of the LSPR phenomenon in metallic NP to improve the light trapping and absorption of small molecule and polymer OPV devices which typically have very thin (*100 nm) absorber layers [3].…”
Section: Introductionmentioning
confidence: 99%
“…For incorporation into the BHJ layer, both small molecule/fullerene and conjugated polymer/fullerene donor acceptor pairs have been studied. Several comprehensive reviews have already been published on these plasmonic OPVs [2,9,16,17]. In general, these prior reviews only discussed the effect of metallic NPs on the PCE of OPV devices when they were added to the device layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These can be used as subwavelength scattering elements to couple a large fraction of incident light into trapped modes within a nearby semiconductor layer. [2][3][4][5][6][7][8][9][10] The surface plasmon resonance (SPR) of metallic nanoparticles depends on the size, shape, and local dielectric environment of the particles. Recently, it has been shown that locating the nanoparticles on the rear of a solar cell is particularly effective in coupling long wavelength light into the cell.…”
mentioning
confidence: 99%